Nonlinear Frequency Response Analysis of Herringbone Gear Pair based on Incremental Harmonic Balance Method - Libang Wang; Hao Dong (Jixie chuandong)
The torsional dynamics model of herringbone gear pair considering time-varying meshing stiffness， constant backlash， dynamic backlash， static transmission error and external dynamic excitation is established. The frequency response characteristics of the system under constant and dynamic backlashes are solved by incremental harmonic balance method， and the results are further verified by Runge-Kutta numerical integration method. The influence of time-varying meshing stiffness， damping， static transmission error and external load excitation on the amplitude frequency characteristics of the system is analyzed. The results show that， there is not only main harmonic response， but also super-harmonic response in the system. The time-varying meshing stiffness and static transmission error can stimulate the amplitude frequency response of the system， while the damping can restrain the amplitude frequency response of the system. Changing the external load excitation has little effect on the amplitude frequency response state change of the system. Compared with the constant backlash， increasing the dynamic backlash amplitude can further control the nonlinear vibration of the gear system.